Actors, Authors, and Authorships in critical qualitative inquiry in Social Work in Critical Times: Critical research in critical times: actors, authorship and authority in the production of knowledge in Social Work - Rubilar Donoso, Gabriela (Critical Proposals in Social Work, 2022)
In this article, we debate and analyze the position of researchers in critical times. To do this, we present the core elements of a research current known as critical qualitative research, its connections with social work, and its debates around knowledge production. We then analyze three approaches to reflection on female actors and authorships, each of which activates a different empirical research experience. This is done to illustrate the elements that we wish to analyze critically and challenge within the context of current research, focusing on debates on knowledge generation and the role of researchers in this process. The contents of this article were reviewed on two prior occasions: a research panel whose members debated methodological aspects of the biographical approach and a disciplinary seminar that articulated knowledge production processes dynamized by the intersection of gender-informed perspectives, generational approaches, and decentralizing points of view on research. The results presented in this article indicate that, in critical times, it is necessary to strengthen reflective strategies for discussing these matters, deemed to be “sensitive” to research and to researchers, develop devices that not only visibilize the voices of the participants of each study, but which also highlight their singular contributions to knowledge production, and generate resistance strategies and efforts to democratize access to the products of social work research in particular and to those of other social science disciplines.